Australian Indigenous environment policy as a deliberative system. Issue 4 (2nd October 2021) - Davis, Roger
ABSTRACT: Despite increased understanding of Indigenous environmental values, governments still fail to respectfully incorporate these values into environmental policy. Deliberative democratic theory can help to better understand this problem. First, by recognising Indigenous democracy as a distinct deliberative system and drawing attention to this 'invisible' democratic contribution to the larger democratic system. Second, the resistance of Indigenous environment policy to openly address Indigenous environmental values, can be understood as weakness in transmission between Indigenous peoples and the settler state. Third, Indigenous deliberative forums linked to the state may help overcome some of these barriers in environment policy. Deliberative democracy draws attention to environmental relations between Indigenous peoples and the state not simply as Indigenous policy making but as democracy making.